Impacto de la configuración de parámetros de antena en un escenario de multiconectividad - De la Bandera Cascales, Isabel; Toril-Genovés, Matías; Pastor Guerrero, Carmen; Barco-Moreno, Raquel (My University, 2021)
New mobile network generation has brought a significant increase in the complexity of the management tasks due to the variety and heterogeneity of services and scenarios. In this new context, network optimization in terms of capacity and coverage becomes essential for operators. This work presents a detailed analysis of the impact of adjusting azimuth and horizontal antenna beamwidth in relation to capacity and coverage in a multiconnectivity scenario. Results show that the modification of these antenna parameters has different effects depending on the network conditions.
Keywords: Redes de antenas; Radio; Tecnología 5G; 5G; Multiconnectivity; Coverage